(untitled) (Jurnal Wicara Desa, 2023)
Kuliah Kerja Nyata (KKN) is a real manifestation of lecturers and students in implementing Tri Dharma Perguruan Tinggi specially the aspect of service. Through community service activities on Pulau Maringkik Village, synergy can be established between the University of Mataram and the people of Maringkik Island as a form of knowledge democracy. The purpose of this service is to provide an understanding to the community about optimizing the promotion of Maringkik Island weaving through a website and based on digital marketing in order to help the government and the local community to develop UMKM to support the village’s economy, as well as address socio-economic issues in the region. Methods of implementing activities include (1) preparation of advocacy and preparation of proposals, (2) planning includes the activities of designing a website prototype and making an activity roadmap, (3) the implementation stage of the website creation program, website launching, and technical guidance on website management, (4) monitoring is carried out to ensure the spread of the website Maringik Island woven fabrics in the community, and (5) An evaluation was carried out to see the number of website visitors and the number of sales during the presence of the website. Apart from that, the KKN group is also involved in other activities, namely teaching the holy qur,an at the posko and TPQ, doing morning exercises, establishing a coastal study center, teaching at SD and SMP Satap Maringkik Island, studying with Maringkik Island children (reading, drawing, and telling stories, Clean Up Day, planting fruit seeds, teaching traditional dances, and mutual cooperation). The results of the activities above show that KKN-T activity has been able to answer some of the problems and needs of the people of Maringkik Island Village which are related to the potential beneficiaries of the village in several socio-economic and social-technological.